Sous vide processed ready-to-cook seerfish steaks: Process optimization by response surface methodology and its quality evaluation. (December 2016) - Singh, Chongtham Baru; Kumari, Namita; Senapati, Sushree Ratnamanjari; Lekshmi, Manjusha; Nagalakshmi, K.; Balange, Amjad K.; Chouksey, M.K.; Venkateshwarlu, G.; Xavier, K.A. Martin
Abstract: The present work was carried out with a goal to optimize the cook-chill conditions of high valued spotted seerfish ( Scomberomorus guttatus ) steaks processed by sous vide method and to evaluate the physico-chemical and microbiological changes during refrigerated storage (3 °C). Response Surface Methodology with Box-Behnken design was employed for optimization. Thiobarbituric acid reactive substances (TBARS) value as the response variable and salt concentration, temperature and cooking time as independent variables were considered in the optimization process. The optimized conditions were found to be; salt concentration 3.5%, temperature 89 °C and cooking time 13.5 min. The sample T1, added with spices was found to be more acceptable compared to T0 (without spices) based on the former's enhanced oxidative stability and sensory characteristics. The trimethylamine (TMA), total volatile basic nitrogen (TVBN) and TBARS values showed a gradual increase during the storage period. All the quality parameters including biochemical, microbiological and sensory evaluation during the refrigerated storage study were found within the acceptable limit till 65 days. The present study demonstrated that the fish steaks processed by optimized conditions of sous vide method can be preserved for 65 days in refrigerated conditions to achieve better market opportunities. Highlights: Ready-to-cook Seerfish steaks was developed with sous vide process. Process parameters were optimized using response surface methodology. Product prepared with spice mix shown better sensory score. The product was acceptable up to 65days.